2020
DOI: 10.1515/cclm-2020-1361
|View full text |Cite
|
Sign up to set email alerts
|

Searching for a role of procalcitonin determination in COVID-19: a study on a selected cohort of hospitalized patients

Abstract: ObjectivesProcalcitonin (PCT) has been proposed for differentiating viral vs. bacterial infections. In COVID-19, some preliminary results have shown that PCT testing could act as a predictor of bacterial co-infection and be a useful marker for assessment of disease severity.MethodsWe studied 83 COVID-19 hospitalized patients in whom PCT was specifically ordered by attending physicians. PCT results were evaluated according to the ability to accurately predict bacterial co-infections and death in comparison with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 35 publications
(45 reference statements)
0
23
1
1
Order By: Relevance
“…Previous studies have demonstrated that although PCT is not a reliable indicator of the presence of concomitant bacterial pneumonia in COVID-19 patients, its absence is assured with a negative predictive value (NPV) of 91.7% or higher. 13 , 14 This was not demonstrated in our critically ill population, where NPV was only 73.2%. Prior research in this area has not targeted ICU patients with COVID-19, likely accounting for the discrepant predictivity of PCT.…”
Section: Discussioncontrasting
confidence: 56%
See 3 more Smart Citations
“…Previous studies have demonstrated that although PCT is not a reliable indicator of the presence of concomitant bacterial pneumonia in COVID-19 patients, its absence is assured with a negative predictive value (NPV) of 91.7% or higher. 13 , 14 This was not demonstrated in our critically ill population, where NPV was only 73.2%. Prior research in this area has not targeted ICU patients with COVID-19, likely accounting for the discrepant predictivity of PCT.…”
Section: Discussioncontrasting
confidence: 56%
“… 6 , 7 , 9 , 21 , 29 Cutoff values of 0.1, 0.25, and 0.5 ng/mL have been used in high quality studies to assess the correlation between PCT and bacterial PNA. 5 , 14 , 22 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A procalcitonin (PCT)guided algorithm could be used to trigger watchful waiting or aid in decreasing prolonged antimicrobial courses [28,29]. However, PCT-based strategies for outcome prognostication and prediction of ICU-acquired infections have not yet been adequately validated in COVID-19 [30,31].…”
Section: Discussionmentioning
confidence: 99%